(3GdehLR aj GdefWbs - (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, CaVd GdOjf CHh YHO Gddg,J (B646 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdNhfLi GdMeO ddg QH GdYGdejf CeG HYO agPG eNJUQ ai Yde GdefWb dNUJg dHYV NdU GUMGHi hSejJg HGdehLR s
(3BNQgG (B:s
(3jfJgi HGdbjGS GdESJKfGFi Hbhdg (B: (3hVY GdCNQ dESJMGdI GdNdh Oaf YcS GdEecGf hdeG hajfG HeG bUOfG PcQg adfNJJe GdcJGH HMeO Gddg s
(3QJHg eDdag Ydi CMO YTQ aUdkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs